Relapsed medulloblastoma in pre-irradiated patients: current practice for diagnostics and treatment - Hill, Rebecca M.; Plasschaert, Sabine L. A.; Timmermann, Beate; Dufour, Christelle; Aquilina, Kristian; Avula, Shivaram; Donovan, Laura; Lequin, Maarten; Pietsch, Torsten; Thomale, Ulrich; Tippelt, Stephan; Wesseling, Pieter; et al. (Cancers, 2022)
Relapsed medulloblastoma (rMB) accounts for a considerable, and disproportionate amount of childhood cancer deaths. Recent advances have gone someway to characterising disease biology at relapse including second malignancies that often cannot be distinguished from relapse on imaging alone. Furthermore, there are now multiple international early-phase trials exploring drug-target matches across a range of high-risk/relapsed paediatric tumours. Despite these advances, treatment at relapse in pre-irradiated patients is typically non-curative and focuses on providing life-prolonging and symptom-modifying care that is tailored to the needs and wishes of the individual and their family. Here, we describe the current understanding of prognostic factors at disease relapse such as principal molecular group, adverse molecular biology, and timing of relapse. We provide an overview of the clinical diagnostic process including signs and symptoms, staging investigations, and molecular pathology, followed by a summary of treatment modalities and considerations. Finally, we summarise future directions to progress understanding of treatment resistance and the biological mechanisms underpinning early therapy-refractory and relapsed disease. These initiatives include development of comprehensive and collaborative molecular profiling approaches at relapse, liquid biopsies such as cerebrospinal fluid (CSF) as a biomarker of minimal residual disease (MRD), modelling strategies, and the use of primary tumour material for real-time drug screening approaches.
Online verfügbar: 28 December 2021
Gesehen am 28.09.2022